Hubungan Pola Asuh Orang Tua dengan Akhlak Remaja di Kampung Jaura RT 001/ 001 Desa Pabuaran Kecamatan Sukamakmur Bogor - Ahmad Syarif; Tri Sumarsih; Ika Kartika (EduInovasi: Journal of Basic Educational Studies, 2023)
The background of this research is that there are many things that affect the morals of adolescents, one of which is parenting, because parents are the closest environment, the first and foremost educator in the family, as well as being a good figure for them. With this background, researchers are interested in examining whether there is a relationship between parenting patterns and adolescent morals. This research was conducted in Kampung Jaura RT 001/001 Pabuaran Sukamakmur Village Bogor. The study population was 155 families, while the sample used was only 50 people with stratified random sampling technique. This study applies the correlation method with the research instrument using a questionnaire. Data analysis using Product Moment correlation technique. The results of this study show r count = 0.610 > r table = 0.278. Thus, HO is rejected and Ha is accepted, which means that there is a relationship between Parenting Patterns and Adolescent Morals. Likewise, the significant test with the t test shows t count 5,339 > t table 2,010. This means that the relationship between parenting and adolescent morals is a significant relationship. Keywords: Relationships, Parenting Patterns, Adolescent Morals.